2004
DOI: 10.1523/jneurosci.4920-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rho Kinase Regulates Schwann Cell Myelination and Formation of Associated Axonal Domains

Abstract: The myelin sheath forms by the spiral wrapping of a glial membrane around an axon. The mechanisms involved are poorly understood but are likely to involve coordinated changes in the glial cell cytoskeleton. Because of its key role as a regulator of the cytoskeleton, we investigated the role of Rho kinase (ROCK), a major downstream effector of Rho, in Schwann cell morphology, differentiation, and myelination. Pharmacologic inhibition of ROCK activity results in loss of microvilli and stress fibers in Schwann ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 65 publications
10
89
1
1
Order By: Relevance
“…Our findings indicate that neither EBP-50 (and by extension, ERM proteins) nor syndecan-3 are required for the proper nodal clustering of axonal proteins. This conclusion does not contradict previously published data (Scherer et al, 2001;Gatto et al, 2003;Goutebroze et al, 2003;Melendez-Vasquez et al, 2004) because ERMs, EBP-50, and syndecan-3 have only been shown to mark the glial processes that are found in conjunction with nodal clusters; there is no evidence that any of these molecules are required for nodal clustering.…”
Section: Channel Subunits In Trembler-j Nodessupporting
confidence: 42%
“…Our findings indicate that neither EBP-50 (and by extension, ERM proteins) nor syndecan-3 are required for the proper nodal clustering of axonal proteins. This conclusion does not contradict previously published data (Scherer et al, 2001;Gatto et al, 2003;Goutebroze et al, 2003;Melendez-Vasquez et al, 2004) because ERMs, EBP-50, and syndecan-3 have only been shown to mark the glial processes that are found in conjunction with nodal clusters; there is no evidence that any of these molecules are required for nodal clustering.…”
Section: Channel Subunits In Trembler-j Nodessupporting
confidence: 42%
“…Interestingly, in Schwann cells of the peripheral nervous system, the Rho-ROCK pathway is not inactivated during myelination as in oligodendrocytes (Melendez-Vasquez et al, 2001). Instead, it is switched on in Schwann cell microvilli, where it seems to play an important role in regulating the myelination of peripheral nerves (Gatto et al, 2003;Melendez-Vasquez et al, 2004). It will now be important to determine how the Rho GTPases are regulated and to identify the neuronal signals that reduce Rho activity in oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…4C,D), as seen in the activation profile of RhoA. Importantly, Rho-kinase is a positive regulator of myelination by Schwann cells in vitro (Melendez-Vasquez et al, 2004). It is possible that Dock7 knockdown leads to indirect upregulation of Rho-kinase and promotes Schwann cell morphological differentiation.…”
Section: Dock7 Knockdown Promotes a Cell-permeable Camp Analog-inducementioning
confidence: 93%
“…Dock7 knockdown shortens the duration of Rac/Cdc42 activation and the downstream activation of JNK, whose signaling negatively regulates Schwann cell differentiation and myelination (Parkinson et al, 2004). Early activation of Rho and Rho-kinase, which positively regulates myelination (Melendez-Vasquez et al, 2004), is also observed to the result from Dock7 knockdown. Furthermore, Dock7 short hairpin (sh)RNA transgenic mice exhibit enhanced myelin thickness, decreased Rac/Cdc42/JNK activity, and increased Rho/Rho-kinase activity in sciatic nerves.…”
Section: Introductionmentioning
confidence: 94%